Democratic Impact of the vague Obligation of Clarity in the Reference re Secession of Quebec - Rocher, François (EUNOMÍA. Revista en Cultura de la Legalidad, 2017)
This article analyses the impact generated by the Reference re Secession of Quebec from a democratic perspective. Following that objective, it focuses on two aspects. The first one proposes a reflexion on the foundations of the Rule of Law, the range of constitutionalism as well as the requests associated to the supremacy of the law and to the understanding of the margin of discretion conferred to political agents. The second one shows up the narrow definition of constitutional democracy proposed by the Court as well as its large grey areas.